Zmanjševanje tveganj za nastanek civilno-vojaških konfliktov - Furlan, Branimir (Sodobni vojaški izzivi, 2018)
Modern and democratic civil-military relations are characterized by equal involvement of senior military leadership into processes for the creation of politics associated with questions on national security and use of armed forces. Civilian and military domains overlap in the process of defining defence and security interests, goals and strategies. Due to different perspectives on national security and defence, and the related role of the armed forces, civil-military tensions are a logical consequence of this process. In most cases, tensions support effective decision making and creation of good security or defence strategies. At certain point, however, tensions may lead to civil-military conflicts and destabilization of civil-military relations. Using different theories of civilmilitary relations and foreign case studies, the author describes circumstances that lead to civil-military conflicts. He describes certain negative effects of implementing civilian control mechanisms, as well as good and bad examples of how both actors in civil-military debate respond to tensions. In order to reduce risks for the development of conflicts and consequently assure the stabilization of civil-military relations, the author highlights, among others, a need for the military leadership to be aware of the supremacy of civilian authorities in debates where consent does not exist, and a need for prudent use of control mechanisms by the civilian authorities.
Keywords: armed forces; civilian control; civil-military conflicts; civil-military tensions; civilni nadzor; civilno-vojaška trenja; civilno-vojaški konflikti; nacionalna varnost; national security; vojska